Rapid crystallization of externally produced ions in a Penning trap - Murboeck,T; Schmidt,S; Birkl,G; Noertershaeuser,W; Thompson,RC; Vogel,M (Physical Review A, 2016)
We have studied the cooling dynamics, formation process, and geometric structure of mesoscopic crystals ofexternally produced magnesium ions in a Penning trap. We present a cooling model and measurements for acombination of buffer gas cooling and laser cooling which has been found to reduce the ion kinetic energy byeight orders of magnitude from several hundreds of eV to μeV and below within seconds. With ion numbersof the order of 1 × 103 to 1 × 105, such cooling leads to the formation of ion Coulomb crystals which displaya characteristic shell structure in agreement with the theory of non-neutral plasmas. We show the productionand characterization of two-species ion crystals as a means of sympathetic cooling of ions lacking a suitablelaser-cooling transition.